Cardiac damage associated with stress hyperglycaemia and acute coronary syndrome changes according to level of presenting blood glucose. (1st October 2015) - Al Jumaily, Talib; Rose'Meyer, Roselyn B.; Sweeny, Amy; Jayasinghe, Rohan
Abstract: Objective: To determine the prevalence of stress hyperglycaemia in people presenting with acute coronary syndrome (ACS), and the relationships between admission glucose and cardiac damage, cardiovascular mortality and morbidity. Methods: In a prospective observational study people presenting with ACS at the Gold Coast Hospital had their admission glucose (AG) level tested to determine stress hyperglycaemia. A range of measurements supplemented this data including troponin levels, category of ACS and major adverse coronary events (MACEs) were obtained through hospital records and patient follow-up post-discharge. Results: One hundred eighty-eight participants were recruited. The prevalence of stress hyperglycaemia in ACS was 44% with 31% having a previous diagnosis of type 2 diabetes and 7.7% had undiagnosed diabetes. The stress hyperglycaemic group had a significantly higher median troponin levels compared to participants with normal blood glucose levels on admission (p < 0.05) however the highest presenting glucose group (> 15 mmol/L) had troponin levels similar to people presenting with normal blood glucose levels and ACS (p > 0.05). Conclusions: Cardiac necrosis as measured by troponin levels is significantly increased in people with ACS and stress hyperglycaemia. This study found that one in four participants presenting with ACS and an admission glucose of > 7.0 had no previous diagnosis for diabetes. Practice implication: Consistently ordering HbA1C testing on patients with high AG can enable earlier diagnosis and treatment of diabetes.